2020
DOI: 10.3389/fneur.2020.00481
|View full text |Cite
|
Sign up to set email alerts
|

Different Therapeutic Effects of CO2 and Diode Laser Irradiation on Tooth Movement-Related Pain

Abstract: Although orthodontic treatment is common, orthodontic force often induced pain. Low-level laser therapy (LLLT) has been investigated to improve therapeutic comfort. In dentistry, LLLT is mainly applied using two types of lasers, CO 2 and diode lasers, whose biological actions are thought to be associated with wavelength (CO 2 : 10,600 nm; diode: 808 nm). The analgesic effect of LLLT on orthodontic treatment-related pain is widely reported but inconsistent. This study aimed to (1) determine whether irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
2
0
0
Order By: Relevance
“…Thus, it is more appropriate to state "initial force". On the whole, however, this tooth-movement animal model has been well-documented and validated by many previous studies, including ours (28)(29)(30). We previously revealed that toothmovement-induced orofacial pain was initiated by a force above 20 g and that pain level differed among rats receiving different force magnitudes (2).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, it is more appropriate to state "initial force". On the whole, however, this tooth-movement animal model has been well-documented and validated by many previous studies, including ours (28)(29)(30). We previously revealed that toothmovement-induced orofacial pain was initiated by a force above 20 g and that pain level differed among rats receiving different force magnitudes (2).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, it is more appropriate to state “initial force”. On the whole, however, this tooth-movement animal model has been well-documented and validated by many previous studies, including ours [ 28 30 ]. We previously revealed that tooth-movement-induced orofacial pain was initiated by a force above 20 g and that pain level differed among rats receiving different force magnitudes [ 2 ].…”
Section: Discussionsupporting
confidence: 66%